PEMANFAATAN STEARIN DALAM PROSES PEMBUATAN SABUN MANDI PADAT - Vonny Indah Sari (Universitas Riau, 2012)
In the crystallization process for manufacturing of cooking oil, there are two products will beproduced, namely liquid phase (cooking oil) and solid phase (stearine). In general stearin produced fromMini Plant Polytechnic Kampar usually just put the sector in a vessel and allowed to stand in an infinitetime, resulted in a bad odor of cracking oil. This study aim to produce a solid soap with compose anappropriate stearin, and meet criteria of SNI 06-3532-1994 on soaps. Parameters determined were thepercentage of stearin, the water content, the number of Alkali-free as NaOH, the amount of fatty acid,free fatty acid and mineral oil. The results show that solid soap was relatively good quality and met theISO, standard which is composed up to 15% of stearine. The solid soap also contained saturated fattyacid of less than 70%, moisture content of 14%, saturated fatty acid content of 54.34%, the alkali contentof 0.03%, FFA levels of 0.33% and no mineral oil found.